Maternal Genotype and Gestational Diabetes - Stuebe, Alison M. (2013)
OBJECTIVE: To determine whether genetic variants associated with glucose homeostasis are associated with gestational diabetes (GDM). STUDY DESIGN: We genotyped 899 self-identified Caucasian women and 386 self-identified African-American women in the Pregnancy, Infection and Nutrition (PIN) Studies cohorts for 36 single-nucleotide polymorphisms (SNPs) associated with type 2 diabetes (T2DM) and/or glucose homeostasis in European populations. RESULTS: GDM was diagnosed in 56 of 899 (6.2%) Caucasian and 24 of 386 (6.2%) African-American women. Among Caucasian women, GDM was associated with carriage of TCF7L2 rs7901695, MTNR1B rs10830963 and GCKR rs780094 alleles associated with T2DM and fasting glucose in non-pregnant populations. Among African-American participants, we found an increased risk among TSPAN8 rs7961581 C allele homozygotes and reduced risk among carriers of the JAZF1 rs864745 T allele. CONCLUSION: We found several SNPs that are associated with GDM risk in the PIN cohorts. Maternal genotyping may identify women at risk for impaired gestational glucose tolerance.